Resilience and Cognitive Flexibility in Boys and Girls from Vulnerable Contexts (Revista de Psicología, 2023)
The objective of the study was to describe and analyze sociocognitive variables related to resilience and cognitive flexibility factors in boys and girls from socially vulnerable contexts. It was a descriptive, non-experimental and cross-sectional study with a quantitative approach. The sample was purposive non-probabilistic, composed of 158 boys and girls from socially vulnerable contexts. The instruments were: Resilience Questionnaire (González Arratia López Fuentes, 2011) and the Concept Formation Subtest (Muñoz Sandoval, et al., 2005). The results indicated positive correlations between cognitive flexibility and resilience factors. Such a finding opens the possibility of focusing psychosocial and educational interventions on strengthening this type of resources.
Keywords: Resilience; Cognitive flexibility; Vulnerability